Management of giant ovarian teratoma - Pradhan, Pramila; Sherpa, Kunsang; Joshi, Anshumala; Pathak, Sabita; Thapa, Meeta; Sharma, Basanta (Journal of Kathmandu Medical College, 2014)
The management of ovarian teratoma in normal condition is well established but in rare giant tumour (diameter over 15 cm) management approaches such as laparoscopy or laparotomy are controversial and may be therapeutically challenging for surgeons. Laparotomic resection is the preferred method for the en-block mass removal, adequate abdominal cavity irrigation, and avoidance of accidental mass rupture during management of giant ovarian teratoma. Here we discuss a case of a 43 year old multiparous lady suffering from a huge ovarian tumour of size 40 cm, admitted in Nepal Medical College Teaching Hospital on 15th May 2013. This patient underwent laparotomy on 21st May 2013 and left sided huge multiloculated ovarian cystic teratoma was removed en-bloc with no complications. DOI: http://dx.doi.org/10.3126/jkmc.v2i2.10632 Journal of Kathmandu Medical College, Vol. 2, No. 2, Issue 4, Apr.-Jun., 2013, page: 89-93